A selective review of selective attention research from the past century. - Driver, Jon (British Journal of Psychology, 2001)
Research on attention is concerned with selective processing of incoming sensory information. To some extent, our awareness of the world depends on what we choose to attend, not merely on the stimulation entering our senses. British psychologists have made substantial contributions to this topic in the past century. Celebrated examples include Donald Broadbent's filter theory of attention, which set the agenda for most subsequent work; and Anne Treisman's revisions of this account, and her later feature-integration theory. More recent contributions include Alan Allport's prescient emphasis on the relevance of neuroscience data, and John Duncan's integration of such data with psychological theory. An idiosyncratic but roughly chronological review of developments is presented, some practical and clinical implications are briefly sketched, and future directions suggested. One of the biggest changes in the field has been the increasing interplay between psychology and neuroscience, which promises much for the future. A related change has been the realization that selection attention is best thought of as a broad topic, encompassing a range of selective issues, rather than as a single explanatory process. Reprinted by permission of the publisher.